Sensory galaxy / Aemillyawaty Abas … [et al.] - Abas, Aemillyawaty; Mazridzuan, Muhammad Arif Azim; Nazri, Nurnasha Izyani; Zainal Abidin, Nor Fadzilla; Yusop, Nur Fitra Azira; Samsol Azaman, Ameer Shahreen (Division of Research and Industry Linkages, 2017)
Sensory Galaxy is a product that allows children to touch the nature without having to actually go out to experience it. The product is meant to help the autism people to improve and strengthen their touch sensory as autism children dislike putting themselves in a dirt and mess. In our product, the children are able to stimulate their touch, taste textures and variety type of sensitivities as they can play with slime, artificial grass, stones and kinetic sand. The product will not lead to messy that the children will not like but as well parents and caretaker can easily monitor their action without hassle that to ensure the safety of the children. There are few benefits of our product is that the product could make the children to adapt the nature such as sands so that they will be comfortable with it as well as could train their sensory stimulation. Besides that, with the new things that they learn by using our product will enhance the new information that they could use it for their everyday task.